Effect of gender, age and season on the distribution Coenurus cerebralis in sheep - Acıöz, M; Bozkaya, F (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of the study was to determine the prevalance of C. cerebralis as well as its sex, age and seasonal distribution in sheep raised in Isparta province of Turkey. The study material consisted of 451 sheep skulls collected from slaughterhouses. The skull of the slaughtered animals was opened with a suitable saw and examined for cerebral and cerebellar coenurosis. C. cerebralis was detected in 25 (5.5%) of 451 sheep skulls that were clinically healthy throughout the year. The parasites were found to be 7.3% in females and 4.2% in males. C. cerebralis was detected in 0.7% in the 0-1 age group, 6.3% in the 1-2 years age group and 10.3% in the 2 years old group. The difference was statistically significant when -the parasite prevalence among the age groups was compared with the chi-square test (p <0.05). The lowest prevalence was determined in February (2.5%) and the highest in July (11.1%). As a result, Coenurosis which is an important problem of sheep breeding, has determined the prevalence in the region of Isparta as 5.5%.